Enhancing communication in healthcare: Supports for interactions between adults with hearing loss and healthcare providers. - Ana Carla Garcia; Ali Arabi; Claire Croteau; Adriana Bender Moreira de Lacerda (PLoS ONE)
Background Communication between a healthcare provider and an adult with hearing loss can be challenging and potentially contribute to health outcomes. To overcome this challenge, researchers have called for urgent multidisciplinary action on communication support in hearing healthcare. Objective This scoping review examines the existing literature on communication support that can be provided to adults with hearing loss during their interactions with healthcare professionals. Methods An online search was conducted using EMBASE, MEDLINE, CINAHL, and PsycINFO. All studies were imported into the Covidence platform for screening. The studies included in this analysis were published in English between 2013 and 2024. Results Twelve articles were included in this review, and seven themes were identified: supportive nonverbal strategies, supportive verbal strategies, human support, environmental and physical adaptations, technological support, education and training, and psychological support and counseling. Conclusions When communicating with a healthcare provider, adults with hearing loss can be assisted through supportive communication strategies.